2023
DOI: 10.3390/agronomy13010266
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Zinc, Iron and Provitamin A Content in Tropical Maize (Zea mays L.)

Abstract: Breeding maize with high contents of zinc, iron and provitamin A (PVA) could be effective in mitigating micronutrient deficiency in developing countries with a high reliance on maize-based diets. Information on the mode of inheritance of zinc, iron, PVA and grain yield (GY) would facilitate the development of varieties with enhanced contents of these nutrients. Twenty-four yellow to orange maize inbred lines and their 96 F1 hybrids generated using North Carolina Design II, were evaluated alongside four checks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…, a genotype HP2 (Harvest Plus) showed 42.21 µg/g. Similar results were also stated byChakraborti et al (2011),Phuke et al (2017),Sharma et al (2021),Qureshi et al (2021),Saletnik et al (2022) andUdo et al (2023). Principle Component Analysis: PC 1: PCA 1 accounts for a significant part of variability among inbred lines and traits which 31.3%.…”
supporting
confidence: 81%
“…, a genotype HP2 (Harvest Plus) showed 42.21 µg/g. Similar results were also stated byChakraborti et al (2011),Phuke et al (2017),Sharma et al (2021),Qureshi et al (2021),Saletnik et al (2022) andUdo et al (2023). Principle Component Analysis: PC 1: PCA 1 accounts for a significant part of variability among inbred lines and traits which 31.3%.…”
supporting
confidence: 81%
“…To assess the existence of sufficient genetic variation in Fe and Zn concentration in tropical maize inbred lines adapted to the lowlands and mid-altitudes, several trials involving different sets of tropical maize inbred lines revealed the presence of significant variation in concentrations of grain minerals among inbred lines in each trial [25]. More recently, multi-environment evaluation of PVA-enriched inbred lines and their hybrids for multiple micronutrients (PVA, Fe, and Zn) identified superior inbred lines and hybrids combining high grain yield with high concentrations of the three micronutrients, demonstrating the possibility of creating nutrient dense maize without affecting grain yield [28].…”
Section: Simultaneous Improvement Of Nutritional Quality Traitsmentioning
confidence: 99%
“…Efforts for multiple enrichments of maize with Fe, Zn, and also provitamin A have been conducted in Nigeria, with the identification of sets of hybrids which combined high Fe and Zn content (24.45 mg kg −1 and 29.24 mg kg −1 ) and average provitamin A content (7.48 mg kg −1 ); however, there was a weak but significant negative correlation between Zn and provitamin A, so the hybrids with the highest provitamin A content were also lowest in Zn content [ 34 ].…”
Section: Research Hotspot: Fe Deficiency and Crops Biofortificationmentioning
confidence: 99%
“…Publications Publications with African Prominent Authorship rice (various Oryza species) [17][18][19][20][21][22][23][24][25][26] [ 17,18,[21][22][23][24][25][26] maize (Zea mays) [27][28][29][30][31][32][33][34] [ [29][30][31][32][33][34] common bean (Phaseolus vulgaris) [35][36][37][38][39][40] [ [37][38][39][40] soybean (Glycine max) [27,41-44] [44] pearl millet (Pennisetum glaucum) [45][46][47][48] [ [45][46][47]…”
Section: Plant Speciesmentioning
confidence: 99%